Inefficiency and Bank Failures: A Joint Bayesian Estimationof a Stochastic Frontier Model and a Hazards Model (2018)
In modeling bank failure, estimating inefficiency separately from the hazards modelresults in inefficient, biased, and inconsistent estimators. We develop a method to si-multaneously estimate a stochastic frontier model and a hazards model using Bayesiantechniques. This method overcomes issues related to two-stage estimation methods,allows for computing the marginal effects of the inefficiency over the probability offailure, and facilitates statistical inference of the functions of the parameters such aselasticities, returns to scale, and individual inefficiencies. Simulation exercises showthat our proposed method performs better than two-stage maximum likelihood, spe-cially in small samples. In addition we find that inefficiency plays a statistically andeconomically significant role in determining the time to failure of U.S. commercialbanks during 2001 to 2010.